Singularly perturbed rank one linear operators - M.E. Dudkin; O. Yu. Dyuzhenkova (Математичні Студії, 2021)
The basic principles of the theory of singularly perturbed self-adjoint operators are generalized to the case of closed linear operators with non-symmetric perturbation of rank one. Namely, firstly linear closed operators are considered that coincide with each other on a dense set in a Hilbert space. The theory of singularly perturbed self-adjoint operators arose from the need to consider differential expressions in such terms as the Dirac $δ$-function. Since it is important to consider expressions given not only by symmetric operators, the generalization (transfer) of the basic principles of the theory of singularly perturbed self-adjoint operators in the case of non-symmetric ones is important problem. The main facts of the theory include the definition of a singularly perturbed linear operator and the resolvent formula in the cases of ${\mathcal H}_{-1}$-class and ${\mathcal H}_{-2}$-class. The paper additionally describes the possibility of the appearance a point of the point spectrum and the construction of a perturbation with a predetermined point. In comparison with self-adjoint perturbations, the description of perturbations by non-symmetric terms is unexpected. Namely, in some cases, when the perturbed by a vectors from ${\mathcal H}_{-2}$ operator can be conveniently described by methods of class ${\mathcal H}_{-1}$, that is impossible in the case of symmetric perturbations of a self-adjoint operator. The perturbation of self-adjoint operators in a non-symmetric manner fully fits into the proposed studies. Such operators, for example, generalize models with nonlocal interactions, perturbations of the harmonic oscillator by the $δ$-potentials, and can be used to study perturbations generated by a delay or an anticipation.